Conference report: Undergraduate family medicine and primary care training in Sub-Saharan Africa: Reflections of the PRIMAFAMED network - Innocent Besigye; Robert Mash; Akye Essuman; Maaike Flinkenflögel (AOSIS, 2017)
Internationally, there is a move towards strengthening primary healthcare systems and encouraging community-based and socially responsible education. The development of doctors with an interest in primary healthcare and family medicine in the African region should begin during undergraduate training. Over the last few years, attention has been given to the development of postgraduate training in family medicine in the African region, but little attention has been given to undergraduate training. This article reports on the 8th PRIMAFAMED (Primary Care and Family Medicine Education) network meeting held in Nairobi from 21 to 24 May 2016. At this meeting the delegates spent time presenting and discussing the current state of undergraduate training at 18 universities in the region and shared lessons on how to successfully implement undergraduate training. This article reports on the rationale for, information presented, process followed and conclusions reached at the conference.